2020
DOI: 10.3389/fneur.2020.01010
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Patterns of Chronic Explosive Breaching in U.S. Military Warfighters

Abstract: Background: Injuries from exposure to explosions rose dramatically during the Iraq and Afghanistan wars, which motivated investigation of blast-related neurotrauma. We have undertaken human studies involving military "breachers"-exposed to controlled, low-level blast during a 3-days explosive breaching course. Methods: We screened epigenetic profiles in peripheral blood samples from 59 subjects (in two separate U.S. Military training sessions) using Infinium MethylationEPIC BeadChips. Participants had varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 103 publications
2
13
0
Order By: Relevance
“…This underscores the utility of DNA methylation not only as a potential risk marker of disease progression, but also as a putative marker of treatment response. Accumulating evidence linking epigenetic mechanisms with response to traumatic stress and the subsequent risk for PTSD [ 47 49 ] fits with our observed observations in Service Members with repeated exposures to blast and blast associated sequalae [ 26 , 31 ]. Similarly, we aim to identify DNA methylation patterns associated with chronic exposures to blast in our Service Members in high-risk occupations, which we will then use to determine MRS predictive of blast exposures in our Veterans.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…This underscores the utility of DNA methylation not only as a potential risk marker of disease progression, but also as a putative marker of treatment response. Accumulating evidence linking epigenetic mechanisms with response to traumatic stress and the subsequent risk for PTSD [ 47 49 ] fits with our observed observations in Service Members with repeated exposures to blast and blast associated sequalae [ 26 , 31 ]. Similarly, we aim to identify DNA methylation patterns associated with chronic exposures to blast in our Service Members in high-risk occupations, which we will then use to determine MRS predictive of blast exposures in our Veterans.…”
Section: Introductionsupporting
confidence: 84%
“…All study procedures involving human participants for Phase 2 were jointly approved by the Colorado Multiple Institutional Review Board (COMIRB) and the JJPVAMC. Because methods being implemented for Phase 1 have already been described [ 26 , 30 , 31 ], we will focus here on Phase 2. However, Phase 1 methods are briefly described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite BMS‐191011 itself having little solubility in water and oral bioavailability, structure–activity relationship studies have explored analogs and cleavable prodrugs with the aim of enhancing solubility while preserving high brain availability and particular BK channel activity (Romine et al., 2007), which hold potential for tinnitus treatment. Apart from BK channels, a recent study identified that different DNA methylation of the KCNN3 (K Ca 2.3, SK3) gene is associated with self‐reported tinnitus in U.S. military warfighters (Wang, Wilson, Ge, et al., 2020). It provides the first evidence of the association of the KCNN3 gene with the human symptom of tinnitus.…”
Section: Calcium‐gated Potassium Channelsmentioning
confidence: 99%